2020
DOI: 10.1017/s0033291720000124
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of autistic and psychotic traits: implications for depression, self-harm and suicidality

Abstract: Background There is increasing interest in the clinical and aetiological overlap between autism spectrum disorders and schizophrenia spectrum disorders, reported to co-occur at both diagnostic and trait levels. Individually, sub-clinical autistic and psychotic traits are associated with poor clinical outcomes, including increased depressive symptomatology, self-harming behaviour and suicidality. However, the implications when both traits co-occur remain poorly understood. The study aimed to (1) examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
2
7
1
Order By: Relevance
“…There has been an increasing interest in the overlap of ASD and prodromal symptoms of psychosis (Chisholm et al, 2015 ; Sampson et al, 2020 ). The shared clinical features among both conditions include unusual thought content, deficits in social interaction, and stereotyped behaviours (De Crescenzo et al, 2019 ; Hommer & Swedo, 2015 ).…”
mentioning
confidence: 99%
“…There has been an increasing interest in the overlap of ASD and prodromal symptoms of psychosis (Chisholm et al, 2015 ; Sampson et al, 2020 ). The shared clinical features among both conditions include unusual thought content, deficits in social interaction, and stereotyped behaviours (De Crescenzo et al, 2019 ; Hommer & Swedo, 2015 ).…”
mentioning
confidence: 99%
“…On the other hand, our correlation analysis also demonstrated a significant relationship between schizotypal traits and self-harm. Such a finding is also interesting, bearing in mind that a recent report found that self-harm was associated with psychotic traits, without specifically addressing schizotypal ones [ 24 ]. In fact, past research has shown that people with these traits are at increased risk for social withdrawal and isolation, which might explain this association [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample consisted of students only and thus may not be representative of the general population. However, by sampling from different universities and fields of study, in which certain traits are clearly more represented (see Table 1), the distribution of these traits in our overall sample might approximate their distribution within the general population (see Sampson et al, 2020). Second, the results of the context adaptation task may be limited by the instructions, which did not explicitly ask participants to draw creative objects, but to draw as many objects as possible.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel line of research stems from the association of underlying cognitive styles with certain psychopathologies, such as autism and schizophrenia, and their expression at nonclinical, personality-variation levels with enhanced creative abilities (Acar, Chen, & Cayirdag, 2018;Fitzgerald & Lyons, 2013). We focus on autistic and positive schizotypal traits-subthreshold features of autism and schizophrenia within the neurotypical population-because they have been proposed to play prominent roles in both divergent thinking (Abu-Akel et al, 2020;Claridge & McDonald, 2009;Crespi, Leach, Dinsdale, Mokkonen, & Hurd, 2016;Jung, 2014) and cognitive control-related processes (Abu-Akel, Apperly, Spaniol, Geng, & Mevorach, 2018;Spaniol, Shalev, & Mevorach, 2018), and because they can co-occur in the same individual (Abu-Akel, Wood, Hansen, & Apperly, 2015;Sampson et al, 2020;Sierro, Rossier, & Mohr, 2016).…”
Section: Introductionmentioning
confidence: 99%